2007
DOI: 10.2460/ajvr.68.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Serial alterations in digital hemodynamics and endothelin-1 immunoreactivity, platelet-neutrophil aggregation, and concentrations of nitric oxide, insulin, and glucose in blood obtained from horses following carbohydrate overload

Abstract: In horses, concurrent increases in venous blood ET-1 immunoreactivity, insulin and glucose concentrations, and platelet-neutrophil aggregates support a role of endothelial dysfunction in the pathogenesis of CHO-induced laminitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…12 Insulin resistance might also predispose horses to laminitis by inducing endothelial cell dysfunction. 51,52 In a recent study in horses, Eades et al 52 determined that digital venous blood endothelin-1 concentrations were significantly higher than baseline values at 11 hours after carbohydrate was administered to induce laminitis. 50 It has previously been shown that endothelin-1 concentrations are higher in laminar connective tissues from horses with laminitis.…”
Section: Discussionmentioning
confidence: 99%
“…12 Insulin resistance might also predispose horses to laminitis by inducing endothelial cell dysfunction. 51,52 In a recent study in horses, Eades et al 52 determined that digital venous blood endothelin-1 concentrations were significantly higher than baseline values at 11 hours after carbohydrate was administered to induce laminitis. 50 It has previously been shown that endothelin-1 concentrations are higher in laminar connective tissues from horses with laminitis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the increased platelet/leukocyte microvascular adhesiveness that is reported in insulinresistant individuals likely augments the participating role of neutrophils in the development of laminitis resulting from endotoxemia, carbohydrate overload, systemic inflammation, and severe gastrointestinal disturbances. 44 Recent experimental work showed that acute laminitis could be directly induced by insulin through maintenance of a supraphysiologic plasma insulin concentration over the course of several days in a euglycemic clamp experiment. 45,46 However, in these experiments, the plasma insulin concentrations that were associated with the development of laminitis significantly exceeded those that are reported for horses and ponies affected with EMS.…”
Section: Recognition and Objective Measurement Of Obesity In Horsesmentioning
confidence: 99%
“…Alterations in endothelial cells have been reported during laminitis in horse (Eades et al, 2007). The end result of altered endothelial function during laminitis may be creation of a pro-inflammatory state (Eades, 2010).…”
Section: Discussion:-mentioning
confidence: 99%